EKSISTENSI PERKEMBANGAN MAZHAB PSIKOLOGI ISLAM SEBAGAI ALIRAN BARU DALAM PSIKOLOGI - Zulkarnain Zulkarnain; Sherly Herdianti (Department of Islamic Psychology, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
This paper explains about of the development of Islamic psychology which the explanation begins with the history of contemporary psychology. Then explain the reasons for the emergence of Islamic psychology. With the development of new schools and theories that emerged. Because it is open to scientists to provide criticism and refinement of existing theories. The presence of the Islamic Psychology school is a form of psychology based on human image according to Islamic teachings, which studies the uniqueness and patterns of human behavior as an expression of the experience of interaction with oneself, the environment, and spiritual nature, with the aim of improving mental health and the quality of religious life on the basis of Islamic noble values to achieve the happiness of living in this world and the hereafter. The existence of this paper is expected to trigger psychology scientists to develop Islamic Psychology according to figures in Muslim thought as a study of behavior and mental life on the basis of theories on understanding the verses of the Qur'an and Sunnah.